Evaluation of vascular trauma after tibial plateau levelling osteotomy with or without gauze protection - Pozzi, A.; Samii, V.; Horodyski, M. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objective: To evaluate the integrity of the cranial tibial artery after performing the tibial plateau levelling osteotomy (TPLO) with or without soft tissue dissection and protection with gauze sponges.Study design: Experimental cadaveric study.Animals: Ten dogs weighing 28 to 35 kg.Methods: Ten pairs of normal pelvic limbs were divided randomly into two groups in which a TPLO was performed with or without soft tissue protection with gauze sponges respectively. Angiography was used to evaluate the integrity of the cranial tibial artery after TPLO in each group. Contrast angiography was performed for each group: 1) before TPLO [Control] 2) after TPLO [Osteotomy] and 3) after intentional laceration of the cranial tibial artery [Arteriotomy]. A ‘yes or no’ was used to score contrast extravasation. The area of extravasated contrast was also calculated on the radiographs. A Mann-Whitney test and an ANOVA with repeated measures were completed to assess the score and the area, respectively, for each of the surgical treatments (Control, Osteotomy, and Arteriotomy) between the conditions of dissection with respect to the cranial tibial artery. A value of p <0.05 was considered significant.Results: The differences between the two groups (with and without protection) for scores and areas of leakage were not significant (p >0.05). However, significant differences were noted between Control and Arteriotomy (p <0.01) and Osteotomy and Arteriotomy (p <0.01), but not between Control and Osteotomy (p >0.05).Conclusions and clinical relevance: A TPLO without protection of the cranial tibial artery can be performed without increased risk of arterial trauma.
Keywords: TPLO; haemorrhage; cranial tibial artery; gauze protection; angiography